Analysis Of Government Policies On Welfare Guarantee Of Religious Court Employees In North Bolaang Mongondow Regency - Supriyatno Waluyo; Sumiyati Beddu; Marwan Djafar (Yayasan pendidikan dzurriyatul Quran, 2026)
This research is motivated by the existence of a gap in the welfare of the State Civil Apparatus (ASN), especially between employees of the Religious Court and the National Land Agency (BPN), even though it is normatively regulated in a uniform national payroll system. This condition shows that there is a difference between formal justice and substantive justice in the ASN remuneration policy. This study aims to analyze government policies in ensuring the welfare of ASN and identify factors that cause income gaps between agencies. This research uses normative legal methods with legislative, conceptual, and comparative approaches. The data used are primary, secondary, and tertiary legal materials that are analyzed qualitatively normatively. The results of the study show that the income gap of ASN is mainly caused by differences in performance allowance policies that are sectoral. This has an impact on differences in income levels, decreased sense of fairness among employees, and reduced participation in the implementation of duties. In addition, other factors that affect the gap include institutional characteristics, particularly in law enforcement functions, as well as community and organizational culture. This gap shows that the ASN remuneration system does not fully reflect the principles of distributive justice and proportionality. Thus, a more integrated and equitable reform of ASN welfare policies is needed to improve the performance and quality of public services.